Comparative analysis of SARS-CoV-2 neutralization titers reveals consistency between human and animal model serum and across assays - Mühlemann, Barbara; Wilks, Samuel H; Baracco, Lauren; Bekliz, Meriem; Carreño, Juan Manuel; Corman, Victor M; Davis-Gardner, Meredith E; Dejnirattisai, Wanwisa; Diamond, Michael S; Douek, Daniel C; Drosten, Christian; Eckerle, Isabella; et al. (Science translational medicine, 2024)
The evolution of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) requires ongoing monitoring to judge the ability of newly arising variants to escape the immune response. A surveillance system necessitates an understanding of differences in neutralization titers measured in different assays and using human and animal serum samples. We compared 18 datasets generated using human, hamster, and mouse serum and six different neutralization assays. Datasets using animal model serum samples showed higher titer magnitudes than datasets using human serum samples in this comparison. Fold change in neutralization of variants compared to ancestral SARS-CoV-2, immunodominance patterns, and antigenic maps were similar among serum samples and assays. Most assays yielded consistent results, except for differences in fold change in cytopathic effect assays. Hamster serum samples were a consistent surrogate for human first-infection serum samples. These results inform the transition of surveillance of SARS-CoV-2 antigenic variation from dependence on human first-infection serum samples to the utilization of serum samples from animal models.